(3eQBI GdeYJHQ aj LHd UHQs - (3YHO GdaJGM Hf eMeO Hf Ydj GdeNdGajs
(3ChdgG (B:s
(3GdMeO ddg GdPi QaY Schf GdCQVhHYO , abO SCdfi ef jLH Ydi faYg Cf CVY dg eDdakG dWjakG ai aVd UjQ , GdLHd GdeTghQ hSejJg eQBI GdeYJHQ ai Mjd UHQ s
(3BNQgG (B:s
(3UQM HPdc dGMGaX GdOjHY ai cJGHg GdeajO HJGQjN RHjO hZjQg ef Cgd GdJGQjN dCf CbShS ai dZI GdjhfGf CHjV hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B7s
(3HgG fXGe GdJYbjHIs
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjf HGdMeQIs
(3cJHJ HQSe LeGd GdESdGe eLdi Hf fGUQ GdCHjV s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdLZQGajG h GdHdOGfs